United Arab Emirates : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper focuses on the real estate market and Expo 2020 in the United Arab Emirates. It discusses the measures that could mitigate risks associated with the real estate cycle and the international experience with real estate booms and hosting large events such as World Expos, Olympic Games, and World Cup tournaments. The paper discusses the recent developments in the segments of the real estate market in Abu Dhabi and Dubai, focusing on changes in sales prices, rents, and supply in the market. It also takes stock of measures the authorities have introduced recently to reduce the potential for speculative pressure in the real estate market.